Bermain dengan Menggunakan Media Toples Pintar (TOPPIN) untuk Meningkatkan Kemampuan Kognitif Anak di TK Masyithoh 04 Kergon Kota Pekalongan - Chafiyah Chafiyah (Action Research Journal, 2021)
In developing classifying objects, they can introduce the concept of numbers (recognize the meaning of numbers and count), introduce the letters of the alphabet, if the child only memorizes the sequence of numbers but cannot understand the immutability of a number, in essence, the child does not know the concept of numbers permanently. Using colorful balls can also introduce colors. For gross motor skills, children can put the ball into the jar. Early childhood learning is child-centered. The learning approach used is a scientific approach which includes a series of processes of observing, asking, gathering information, reasoning, and communicating. The whole process is carried out using all the senses as well as various sources and learning media. By playing using Media Smart Toples (TOPPIN) encourages children to have the potential to develop in further education.